MEMBACA MAQASHID SYARI’AH DALAM PROGRAM BIMBINGAN PERKAWINAN - Ihtiar, Habib Wakidatul (IAIN Tulungagung, 2020)
The government has established a strategic policy in the framework of printing happy and prosperous marriage ties in accordance with the guidance of religion and state regulations. The policy is to organize a marriage guidance program for prospective brides. The implementation of marriage guidance contains a great intention and hope to realize the shared ideals in fostering a marriage and family life that is sakinah, mawaddah and rahmah. The rise of cases and family problems, such as divorce, quarreling, domestic violence, also formed the background for this policy. Marriage guidance as an instrument in printing individuals who are ready to navigate marital ties, have the same direction and substance as the principles of Islamic teachings. This can be examined from the aspects of the maqashid syari’ah. So that its existence and role is needed by the community, especially the bride and groom. Keywords: Maqashid Syari’ah, Marriage Guidance.